The Effect of Capital Adequacy Ratio (CAR) and Debt to Equity Ratio (DER) on Return On Asset (ROA) in State-Owned Banks Listed on the Indonesia Stock Exchange - Wahyu, Didin Rasyiddin; Sofyani, Fitri; Munawaroh, Munawaroh; Widodo, Wahyu; Komarudin, Mamay (LPPM Universitas Bina Bangsa, 2024)
Increasingly fierce business competition requires banks to increase competitiveness in attracting investors. Investors before investing their funds need information about the company's performance. The use of bank financial statements requires information that can be understood, relevant, and can be compared to evaluating the bank's financial position and performance as well as being useful in economic decision-making. This study was conducted to find out whether the Capital Adequacy Ratio (CAR) and Debt To Equity Ratio (DER) have an effect on Retrun On Asset (ROA) in state-owned banks for the period 2015 – 2022. The method used in this study is a quantitative method. The population in this study is state-owned banks listed on the Indonesia Stock Exchange (IDX) for the period 2015 – 2022. The population used by 4 banks. The number of samples studied was 32 obtained from 4 banks multiplied by 8 years of financial statements. The analysis technique used is multiple linear regression which includes classical assumption tests, as well as partial tests (t-test) and simultaneous tests (F-test) with a significant level () = 0.05 percent. The data was tested using the help of IBM SPSS version 26 software and Microsoft Excel. The results of the study show that the hypothesis of the t-test is a significant value (Sig) for the CAR variable of 0.009 < 0.05, and t-count (2.792) > t-table (2.04227), so the Capital Adequacy Ratio (CAR) has an influence on Return On Asset (ROA). The significant value (Sig) for the DER variable is 0.000 < 0.05, and the t-count (-4.159) < t-table (2.04227), so the Debt to Equity Ratio (DER) has no effect on the return on asset (ROA) of the stock. For the F test, which is a significant value of 0.000 < 0.05, and F-count (21.509) > F-table (3.34), then simultaneously there is an influence on Return On Asset (ROA). The conclusions obtained in this study show that the Capital Adequacy Ratio (CAR) partially affects Return On Asset (ROA), while Debt to Equity Ratio (ROA) has no effect on Return On Asset (ROA). Simultaneously, the Capital Adequacy Ratio (CAR) and Debt to Equity Ratio (DER) have an effect on Return On Asset (ROA)